2017
DOI: 10.7150/jca.19173
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil-Lymphocyte Ratio Predicts Recurrence of Cervical Intraepithelial Neoplasia

Abstract: OBJECTIVE: The purpose of the present study was to determine the prognostic significance of the neutrophil-lymphocyte ratio (NLR) in recurrence of cervical intraepithelial neoplasia (CIN).METHODS: We evaluated the NLR as a prognostic marker in the entire cohort of 230 patients who had undergone surgical resection and were diagnosed with CIN. Subjects were categorized into two different groups based on the NLR (NLR-high and NLR-low) using cutoff values determined by receiver operating characteristic (ROC) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 43 publications
0
24
2
Order By: Relevance
“…Nakamura et al found that the progression free and overall survival hazard ratio of 0.317 (95% confidence interval (CI): 0.167 0.602; P<0.001) and 0.274 (95% CI:0.141-0.530; P<0.001), respectively (Nakamura et al, 2018). Chun S. et al found a similar finding with the recurrence free survival hazard ratio of cervical intraepithelial neoplasia for 7.66(95% CI 2.34-25.1, p=0.001) (Chun et al, 2017). Moreover, the NLR can provide a valid prediction on the prognosis of the patient with stage IIB and the metastasis of the lymph nodes.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Nakamura et al found that the progression free and overall survival hazard ratio of 0.317 (95% confidence interval (CI): 0.167 0.602; P<0.001) and 0.274 (95% CI:0.141-0.530; P<0.001), respectively (Nakamura et al, 2018). Chun S. et al found a similar finding with the recurrence free survival hazard ratio of cervical intraepithelial neoplasia for 7.66(95% CI 2.34-25.1, p=0.001) (Chun et al, 2017). Moreover, the NLR can provide a valid prediction on the prognosis of the patient with stage IIB and the metastasis of the lymph nodes.…”
Section: Discussionmentioning
confidence: 72%
“…Lee et al, (2012) have suggested the use of NLR for estimating the mortality and the recurrences of cervical cancer. A high NLR is correlated with the poor prognosis of cervical carcinoma patients (Nakamura et al, 2018;Chun et al, 2017;Nakamura et al, 2015). The pretreatment NLR level is inversely correlated with the survival time in the cervical carcinoma patients (R=-0.538, R2=-0.289, P=0.002).…”
Section: Discussionmentioning
confidence: 94%
“…In the current study, NLR and total WBC count were known to be prognostic factors for predicting the likelihood of recurrence in patients who underwent excisional procedure for CIN. Chun et al, (2017) investigated the relationship between NLR and recurrence of CIN in Korea. They studied 230 patients who underwent excisional procedure for CIN.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated to detect the hazard ratio of 3.54 for the risk of recurrence of NLR 2.1 (Chun et al, 2017) with power of 80%, alpha of 0.05, and attrition rate of 10 percent. The required sample size was calculated to be at least 301 patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation